Temporal trends of case-fatality in patients undergoing dual-injection coronary chronic total occlusion recanalization - Blessing, Recha Ruth Liselotte; Keller, Karsten; Dimitriadis, Zisis; Münzel, Thomas; Gori, Tommaso; Hobohm, Lukas (Clinical research in cardiology, 2023)
Recently, interventional techniques and material to treat chronic total occlusion (CTO) with percutaneous coronary intervention (PCI) have evolved significantly. Nevertheless, it is still unknown whether this progress improved treatment success and patients’ outcome. In a nationwide sample, we sought to analyze trends of patients’ characteristics, complications and in-hospital case-fatality of patients undergoing CTO revascularization in Germany.
Online veröffentlicht: 11. September 2023
Gesehen am 29.11.2023